Driving Factors on Greenhouse Gas Emissions in Permafrost Region of Daxing'an Mountains, Northeast China. Issue 3 (15th March 2022) - Gao, Weifeng; Gao, Dawen; Cai, Tijiu; Liang, Hong
Abstract: Permafrost regions are an important source of greenhouse gases. However, the effects of different permafrost wetland types on greenhouse gas emissions and the driving factors are still unclear in the permafrost region. Here, we selected three typical permafrost wetlands from the Daxing'an Mountains to investigate the effects of permafrost wetland types on greenhouse gas emissions. The cumulative N2 O, CO2, and CH4 emissions were 84–122, 657, 942–1, 446, 121, and 173–16, 924 kg km −2, respectively. The linear mixed effects model indicated that N2 O emissions were significantly affected by the NO3 − ‐N content, whereas CO2 emissions were mainly driven by soil temperature, water table level, and NO3 − ‐N content. CH4 emissions were affected by soil temperature and water table level. Permafrost wetland types significantly affected the average and cumulative N2 O, CO2, and CH4 emissions. The cumulative N2 O emissions were highest in the Larix gmelinii ‐ Carex appendiculata ( LC ) wetland and lowest in the Betula fruticosa Pall. ( B ) wetland, driven by NO3 − ‐N content. The cumulative CO2 emissions were highest in the B wetland and lowest in the L. gmelinii ‐ Ledum palustre var. dilatatum ( LL ) wetland. The cumulative CH4 emissions from B wetland were significantly higher than those from LL and LC wetlands. The differences in cumulative CO2 and CH4 emissions were driven by the water table level. Our findings indicate that NO3 − ‐N content affect the spatial‐temporal variation of N2 O emissions, whereas water table level influence the spatial‐temporal variation of CO2 and CH4 emissions in the permafrost region of the Daxing'an Mountains. Plain Language Summary: The permafrost region of the Daxing'an Mountains is a source of greenhouse gas emissions, releasing 84–122 kg N2 O km −2, 657, 942–1, 446, 121 kg CO2 km −2, and 173–16, 924 kg CH4 km −2 during the growing season. The N2 O emissions are mainly a result of denitrification, which is significantly affected by the NO3 − ‐N content. The CO2 emissions from the three wetland types showed similar temporal variations and were driven by soil temperature, water table level, and NO3 − ‐N content. The temperature sensitivity of CO2 release ( Q 10 ) from the Daxing'an Mountains was lower than that of most other permafrost regions. With changes in the water table level, the wetlands become either a sink or a source of CH4, which is affected by soil temperature and water table level. The different permafrost wetland types significantly influenced the average and cumulative N2 O, CO2, and CH4 emissions. The cumulative N2 O emissions were mainly driven by NO3 − ‐N, whereas the cumulative CO2 and CH4 emissions were both driven by the water table level. The GWP of the wetlands ranged from 691, 326 to 1, 941, 338 kg CO2 ‐eq km −2 . Key Points: The permafrost region of Daxing'an Mountains was a source of greenhouse gas emissions and global warming potential Permafrost wetland types significantly influenced on N2 O, CO2, and CH4 emissions, which were mainly driven by NO3 − ‐N or water table level